Analisa Keekonomian Pada Proyek Injeksi Surfaktan Sumur 04 Lapangan Delima Dengan Menggunakan Psc Cost Recovery - Erika Maulina; Firdaus; Eka Megawati; Ali Muchammad; Abdi Suprayitno; Kartika Choriah; Darmiyati, Iin (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2023)
The role of fossil energy such as oil, natural gas, and coal in various economic activities is currently irreplaceable and has become a major need for the Indonesian people. The increasing needs of the community are sometimes not proportional to the results of the amount of production, as happened at Well 04 in the Delima Field, need surfactant injection because the production flow rate is decreasing. The purpose of conducting an economic analysis on this surfactant injection project is to detrmine whether choosing a surfactant injection method will produce appropriate profits. The system used in this economic analysis is PSC Cost Recovery using economic indicators NPV, IRR, POT, and Benefit to Cost. For sensitivity analysis using NPV Contractor, IRR Contractor, Contractor Take, and Government Take. Based on the results of calculations that have been carried out, the net profit value received by the contractor is 13.359.765 US and that received by the government is 16.420.258 US. While the results of the sensitivity analysis that has been carried out, it is known that the most influential parameters are cumulative production and oil prices which are directly proportional.